Are PrEP services in France reaching all those exposed to HIV who want to take PrEP? MSM respondents who are eligible but not using PrEP (EMIS 2017). Issue 2 (13th May 2020) - Annequin, Margot; Villes, Virginie; Delabre, Rosemary M.; Alain, Tristan; Morel, Stéphane; Michels, David; Schmidt, Axel Jeremias; Velter, Annie; Rojas Castro, Daniela
ABSTRACT: Pre-exposure prophylaxis (PrEP) is fully reimbursed by the French health insurance system since 2016. However, uptake of PrEP is slower than expected and little is known about men who have sex with men (MSM) who are eligible for PrEP according to French guidelines, but not using it. This study aims to (1) assess and describe MSM that are eligible to PrEP but not using it, and (2) identify potential individual and structural barriers of PrEP uptake among eligible MSM who are aware and intend to take PrEP. Data from EMIS-2017, a cross-sectional internet survey among gay, bisexual, and other MSM, were used. Among 7965 respondents without diagnosed HIV, 9.2% were PrEP users. Among 7231 non-PrEP users, 35.2% were eligible to PrEP and 15.2% were eligible, aware and intended to take PrEP. Eligible MSM who are not using PrEP are mostly younger, students, less "out", living in small cities, using condoms more frequently but still with low self-efficacy regarding safe sex and more distant from preventive health care and information than PrEP users. Despite free PrEP availability in France, results suggest that PrEP is not fully accessible and that there is a need to increase PrEP demand and decentralize PrEP delivery.